2020
DOI: 10.1108/ijlls-05-2020-0022
|View full text |Cite
|
Sign up to set email alerts
|

Lesson study as a vehicle for improving SEND teachers’ teaching skills

Abstract: PurposeCollaborative professional development for inclusive teaching is a limited area of research, although there is an extensive need for special educational needs and disabilities (SEND) teachers. Research findings of how teachers’ professional development can contribute to support the development of powerful learning situations for all students are presented in this special issue. The aim is to contribute to the knowledge of how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 29 publications
1
10
0
8
Order By: Relevance
“…Empirical evidence has shown that the main difficulties concerning the operationalisation of an inclusive school culture have referred, in recent years, to the adequate training and preparation of the teacher and preservice teachers, both for the common class and for specialists (Watkins, 2012;European Agency for Special Needs and Inclusive Education, 2014;Ibe-Unesco, 2016;Simón et al, 2018;Botes et al, 2020), the need for changes in pedagogical practices (Aas, 2020;Holmqvist, 2020;Norwich et al, 2021), and, consequently, the educational process, which generally has sought to focus on students with different disabilities and special needs, rather than explore their full potential (Florian, 2019;Aas, 2020;Schlünzen et al, 2020). In addition, there is a body of research demonstrating that barriers to inclusion also include the lack of adaptation in the physical and architectural structure of the environment and accessibility in different aspects, especially the technological one (Almaiah et al, 2020;Beaunoyer et al, 2020;Dhawan, 2020;Leifler, 2020;Kim et al, 2021), and school leaders´ lack of knowledge about how to implement the aspects included in public policies (Schlünzen et al, 2020).…”
Section: Inclusive Education and The Ccm Approachmentioning
confidence: 99%
“…Empirical evidence has shown that the main difficulties concerning the operationalisation of an inclusive school culture have referred, in recent years, to the adequate training and preparation of the teacher and preservice teachers, both for the common class and for specialists (Watkins, 2012;European Agency for Special Needs and Inclusive Education, 2014;Ibe-Unesco, 2016;Simón et al, 2018;Botes et al, 2020), the need for changes in pedagogical practices (Aas, 2020;Holmqvist, 2020;Norwich et al, 2021), and, consequently, the educational process, which generally has sought to focus on students with different disabilities and special needs, rather than explore their full potential (Florian, 2019;Aas, 2020;Schlünzen et al, 2020). In addition, there is a body of research demonstrating that barriers to inclusion also include the lack of adaptation in the physical and architectural structure of the environment and accessibility in different aspects, especially the technological one (Almaiah et al, 2020;Beaunoyer et al, 2020;Dhawan, 2020;Leifler, 2020;Kim et al, 2021), and school leaders´ lack of knowledge about how to implement the aspects included in public policies (Schlünzen et al, 2020).…”
Section: Inclusive Education and The Ccm Approachmentioning
confidence: 99%
“…Studies for sustainability are also in line with the keyword in LS, namely "continuous improvement" (Babcock et al, 2011;Hunter & Back, 2011). However, in LS the collaboration and networking aspects are the main things (Holmqvist, 2020;Lomibao, 2016;Stokes et al, 2020;Takahashi, 2014;Takahashi & McDougal, 2016). Especially for networking, Nurwidodo et al (2018) recommends the following "In order for LSLC to manifest and become successful, resourcing and utilizing the partnership with schools are required.…”
Section: Figure 2 Kite Diagram Of Lslc Program In Batu Citymentioning
confidence: 99%
“…One of the new ways to use Lesson Study is to work in teams as teacher educators, where the participants in this activity are teachers and not students or students in a normal school environment. (Holmqvist, 2020). Lesson Study aims to create a more positive learning situation.…”
Section: Application Of Lesson Studymentioning
confidence: 99%